Impact of Indian Climate in Terms of Temperature Humidity Index on Reproductive and Semen Parameters of Barbari Bucks - Shastri, Shriya; Chouksey, Shivika; Chourasiya, Mona; Nidhi Shukla, Satya (The Indian Journal of Animal Reproduction, 2025)
The present study was conducted to investigate the effect of temperature-humidity index on the reproductive and semen parameters of Barbari bucks. Twelve adult Barbari bucks aged between 1.5 to 4.0 years were selected and managed under a semi-intensive system. A total of 288 ejaculates were collected from the chosen bucks during the experiment. Detailed sexual characteristics and breeding behaviors were recorded during semen collection. Immediately after collection, the initial evaluation of the semen samples was carried out within 10 min, and then the sample was diluted with a Tris-based semen extender (TCEYG Buffer). The temperature humidity index (THI) was calculated to evaluate its effect on reproductive parameters. The result reveals that there was mild stress in the August and September months, whereas no stress was seen in other months of the study period. Correlation between climatic parameters with different semen parameters and the data showed that relative humidity was highly significant (p ≤ 0.01) and negatively correlated with pH. However, other climatic parameters were negatively correlated with seminal parameters.